2017
DOI: 10.1007/s11136-017-1557-x
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life (HRQoL) and its correlates among community-recruited children living with HIV and uninfected children born to HIV-infected parents in West Bengal, India

Abstract: Purpose Helping children living with HIV (CLH) to attain an optimum quality of life is an important goal for HIV programs around the world. Our principal objectives were to determine the association of HIV infection with different domains of health-related quality of life (HRQoL) among 8- to 15-year-old CLH in India and to compare the HRQoL parameters between CLH and HIV-negative children born to HIV-infected parents (“HIV-affected”). We also assessed whether anti-retroviral therapy (ART) and CD4 lymphocyte co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Therefore, understanding the relationship between mothers' perceived HIV-related stigma and the health among their children is crucial [36], especially when both mother and child live with HIV, which may compound consequences of HIV-related stigma. In India, maternalchild HIV research is focused primarily on prevention of mother-to-child transmission [37], with few studies exploring mother and/or caregiver-child dyads outside the context of transmission prevention [38], and even fewer studies investigating mother-child HIV seroconcordant dyads [39]. Borrowed from epidemiological studies regarding HIV transmission risk in intimate relationships [40] where seroconcordance describes relationships where couples are both HIV positive, we extend the concept of seroconcordance beyond intimate couples to include HIV-positive mother-child dyads.…”
Section: Hiv and Stigmamentioning
confidence: 99%
“…Therefore, understanding the relationship between mothers' perceived HIV-related stigma and the health among their children is crucial [36], especially when both mother and child live with HIV, which may compound consequences of HIV-related stigma. In India, maternalchild HIV research is focused primarily on prevention of mother-to-child transmission [37], with few studies exploring mother and/or caregiver-child dyads outside the context of transmission prevention [38], and even fewer studies investigating mother-child HIV seroconcordant dyads [39]. Borrowed from epidemiological studies regarding HIV transmission risk in intimate relationships [40] where seroconcordance describes relationships where couples are both HIV positive, we extend the concept of seroconcordance beyond intimate couples to include HIV-positive mother-child dyads.…”
Section: Hiv and Stigmamentioning
confidence: 99%
“…Participants for the qualitative study were recruited through a convenience sample of CLH and their caregivers residing in the Paschim and Purba Medinipur districts of West Bengal (Das, 2015). Principal caregivers of CLH were requested to participate in IDIs, while CLH took part in FGDs with other CLH in their age group.…”
Section: Methodsmentioning
confidence: 99%
“…In India, where even normal uninfected children are often deprived of basic amenities and social support, ensuring quality of life for children living with HIV (CLH) is an especially arduous task. Widespread discrimination associated with HIV and lack of parental care (for orphans) compound the problem even further (Das, 2015; Turan and Nyblade, 2013). Therefore, a culturally appropriate tool to assess HRQoL will be helpful in identifying the areas of concern among the pediatric HIV population and to formulate interventions to address their specific needs.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on the HRQoL of children with HIV infection have shown equivocal findings [ 4 , 6 , 11 - 14 ]. While some authors found significantly lower quality of life among HIV-infected children when compared to healthy control [ 11 , 12 ], others found no significant associations [ 4 , 9 , 13 , 14 ]. With regards to predictors of HRQoL, there is some evidence for some socio-demographic variables such as socioeconomic status [ 15 , 16 ], clinical factors such as being on antiretroviral medications [ 6 , 17 ], disease severity [ 4 , 17 ], and nutritional indices predicting health-related quality of life [ 18 - 20 ].…”
Section: Introductionmentioning
confidence: 99%